A comparative study of the analytical methods for the determination of polycyclic aromatic hydrocarbons in seafood by high‐performance liquid chromatography with fluorescence detection. (30th December 2013) - Yoo, Miyoung; Lee, Sanghee; Kim, Sunyoung; Kim, Su‐ji; Seo, Hye‐young; Shin, Dongbin
Summary This study was performed to establish a rapid analytical method to determine the presence of fourteen polycyclic aromatic hydrocarbons (PAHs) in seafoods by high‐performance liquid chromatography with fluorescence detection (HPLC/FLD). The samples were prepared using two methods: the Quick, Easy, Cheap, Effective, Rugged, Safe (QuEChERS) method and the alkali digestion method. The QuEChERS method involved a convenient and effective solid–liquid extraction and a simple purification. The alkali digestion method was comprised of a liquid–liquid extraction after saponification with potassium hydroxide followed by purification. The limits of detection (LODs) and limits of quantification (LOQs) of the QuEChERS method ranged from 0.05 to 1.60 μg kg−1, and those of the alkali digestion method ranged from 0.28 to 5.18 μg kg−1. The repeatability for all target analytes was similar for the two methods, that is, 0.66–4.24% and 0.26–5.75% for the QuEChERS and alkali digestion methods, respectively. At analyte concentrations of 2.5–50 μg kg−1, the recovery of the QuEChERS method ranged from 86.87% to 115.67% and that of the alkali digestion method ranged from 69.22% to 100.21%.